CULTURAL POSSIBILITIES OF GOLDEN MAHSEER TOR PUTITORA (HAM.) IN HIMALAYAN UPLANDS - ., SHYAMSUNDER; RAINA, H.S.; MOHAN, MADAN; JOSHI, C.B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
For the rehabilitation and conservation of threatened golden mahseer (Torputitora) fishery from himalayan uplands, approximately 1.12 lakhs advanced fry have been produced so far in a flow-through hatchery established in Kumaon himalaya and stocked in various biotopes. An experimental attempt has also been made to rear the mahseer fry 0.200 g to 105 g fish in about 240 days under pond environment in Tarai region of Uttar Pradesh. Future research strategies to culture the species in captivity have been highlighted in the paper.